Transforming Consumer Goods: Strategic Approaches to Digital Innovation and Competitive Advantage - Algarhy, Mohammad Hasan (Journal of Global Economy, Business and Finance, 2025)
The consumer goods industry is undergoing a digital transformation driven by emerging technologies like IoT, AI, and big data analytics. This impacts supply chains, manufacturing, product development, e-commerce, delivery, and customer experience. Companies leveraging personalization strategies through algorithms and customer data analysis are driving customer loyalty and sales growth. Sustainability initiatives and "Buy Now, Pay Later" policies are also influencing sales. Companies prioritizing personalized customer experiences through digital channels, fostering effective management, strong promotional activities, and user-friendly frameworks will have a competitive advantage. Automation, strategic management, quality maintenance, and agile replenishment technologies are essential for achieving smart industry and supply chain efficiency.